Quality of experience in mobile applications: A systematic mapping of metrics and tools - Collazo Garcia, Antonio (2020)
Context: Quality of Experience (QoE) enables the description of user perceptions about the performance of a particular application or service. In the mobile computing context, it is an important measure for service providers and users, since QoE makes it possible to improve it and make it more competitive to achieve user fidelity. In turn, the importance of QoE in mobile technologies increases due to the various factors that affect the applications that run on mobile devices. Objective: The purpose of this study is to identify the metrics and tools relevant to the scientific community for the QoE analysis of mobile applications. Method: A systematic mapping study was conducted. Results: From a total of 751 studies, 33 were selected, and 13 metrics and 15 mobile QoE analysis tools were identified. Conclusions: The existing mobile QoE analysis tools collect and calculate metrics automatically, combining objective and subjective metrics. However, they present limited approaches, making it difficult to carry out an integral analysis of the applications.